Safety and efficacy of abacavir for treating infants, children, and adolescents living with HIV: a systematic review and meta-analysis. (October 2022) - Jesson, Julie; Saint-Lary, Laura; Revegue, Marc Harris Dassi Tchoupa; O'Rourke, John; Townsend, Claire L; Renaud, Françoise; Penazzato, Martina; Leroy, Valériane
Summary: Background: Abacavir is a nucleoside reverse transcriptase inhibitor recommended in paediatric HIV care. We assessed the safety and efficacy profile of abacavir used in first, second, or subsequent lines of treatment for infants, children, and adolescents living with HIV to inform 2021 WHO paediatric ART recommendations. Methods: In this systematic review and meta-analysis, we included observational and experimental studies conducted in infants aged 0–1 year, children aged 1–10 years, and adolescents aged 10–19 years living with HIV; with data on safety or efficacy, or both, of abacavir-based antiretroviral therapy (ART); published in English or French between Jan 1, 2009, and Oct 1, 2020, plus an updated search to incorporate studies published between Oct 1, 2020, and May 15, 2022. Studies could be non-randomised or non-comparative and include patients who are treatment-naive or those who previously received abacavir (only if abacavir was combined with other ART). Case studies, studies in adults aged 18 years or older, and those assessing the effect of maternal ART exposure were excluded. We extracted data related to study identifier, study design, study period, setting, population characteristics, ART treatment, and safety (any hypersensitivity reaction, death, grade 3 or 4 adverse events, treatment discontinuation, any other morbidities, and serious adverse events), and efficacy outcomes (HIV viral load and CD4 counts reported at 6 and 12 months after ART initiation). Using random-effect models, we estimated weighted pooled incidence and relative risk (RR) of outcomes. The protocol is published in PROSPERO (CRD42022309230). Findings: Of 1777 records identified, 1475 (83%) were screened after removing duplicates and a further 1421 (96%) were excluded. Of 54 full-text articles assessed for eligibility, 33 (61%) were excluded. Four records were identified from grey literature plus one duplicate from database searching, resulting in 24 studies included (two randomised controlled trials, one single-arm trial, 12 prospective cohorts, seven retrospective cohorts, and two cross-sectional studies). 19 studies described safety data and 15 described efficacy data. 18 (75%) studies were conducted in ART-naive participants. The risk of bias was considered moderate to high for most studies, and all outcomes had significant between-study heterogeneity. Data from 24 265 participants were included, of whom 7236 (30%) received abacavir. Abacavir hypersensitivity reaction was reported in nine (38%) studies, with an incidence ranging from 0·00% to 8·26% ( I 2 =85%; p<0·0001). The incidence of death (reported in seven studies) following abacavir treatment varied from 0·00% to 5·49% ( I 2 =58%; p=0·026). Viral suppression (<400 copies per mL) varied from 50% to 70% at 6 months ( I 2 =92%, p<0·0001) and from 57% to 78% at 12 months ( I 2 =88%, p<0·0001). Interpretation: Toxic effects due to abacavir use remain rare and manageable. Despite scarce data on efficacy, this meta-analysis supports the use of abacavir as a preferred first-line regimen for infants and children living with HIV. Funding: WHO.